ATTITUDES OF UNIVERSITY FACULTY TOWARD INCLUSION OF STUDENTS WITH SPECIAL EDUCATION NEEDS - Teresita Dinoc Ignacio; Keven John Ngao-i Allit (Erudio Journal of Educational Innovation, 2023)
Inclusive education is an educational approach that has become a worldwide phenomenon. Accordingly, most of the studies conducted on teachers’ attitudes toward inclusive education are quantitative in nature. Hence, this study explored the attitudes of university faculty toward the inclusion of students with special needs. This qualitative study employed the phenomenological research design. The participants in the study who were identified through purposive sampling involved fourteen (14) university faculty. The inclusion criteria for the key informants considered those faculty without formal education and training background in special education but with experience in teaching college students with special needs. The data gathering was done through a semi-structured interview that lasted for an hour or more. This method of data-collection allowed the researchers to ask follow-up questions to saturate the information from the participants. The interview questions were guided through an aid memoire that was developed based on an a priori code. Audio recordings and field notes were used to help the researchers in the transcription of the data. A member check was conducted with the key informants after the transcription of their interviews to observe the correctness and novelty of the collected data. Through the cool and warm analyses of the data, three themes emerged, namely: a) being egalitarian, b) being sensitive, and c) being accountable. The themes that emerged from the analyses of the gathered data show that the university faculty have positive attitudes toward students with special needs.